Artefact-free late gadolinium enhancement imaging in patients with implanted cardiac devices using a modified broadband sequence: current strategies and results from a real-world patient cohort. Issue 5 (18th April 2017) - Hilbert, Sebastian; Weber, Alexander; Nehrke, Kay; Börnert, Peter; Schnackenburg, Bernhard; Oebel, Sabrina; Spampinato, Ricardo; Rogge, Cathleen; Richter, Sergio; Hindricks, Gerhard; Paetsch, Ingo; Jahnke, Cosima
Abstract: Aims: Cardiac magnetic resonance (CMR) imaging in patients with implanted cardiac devices is often limited by device-related imaging artefacts. Limitations can potentially be overcome by employing a broadband late gadolinium enhancement (LGE)-CMR imaging technique. The purpose of this study was to investigate the relationship between implanted cardiac devices and the optimal frequency offset on broadband LGE-CMR imaging to increase the artefact-free visibility of myocardial segments. Methods and results: A phantom study was performed to characterize magnetic field disturbances related to 15 different cardiac devices. This was complemented by B0 and B1 +  imaging of three different device types in four healthy volunteers. Findings were validated in 28 patients with an indication for arrhythmogenic substrate characterization before catheter ablation. In the phantom study, the placement of a PM, implantable cardioverter-defibrillator (ICD) or CRT-D generator led to a significant impairment of the radiofrequency field. B0 mapping in phantom and volunteers showed the highest off-resonance maximum with CRT-D systems with the maximum off-resonance significantly decreasing for ICD or PM systems, respectively. In all patients, with conventional LGE imaging 73.1% (61.5–92.3%) of LV segments were free of device-related artefacts, while with the broadband LGE technique, a significant increase of artefact-free segments was achieved [96.4% (85.7–100%); P  = 0.00008]. Conclusion: Using a modified broadband sequence for LGE imaging significantly increased the number of artefact-free myocardial segments thereby leading to improved diagnostic value of the CMR exam. Since the occurrence and extent of hyperintensity artefacts are closely related to the individual device, more studies are warranted to evaluate if the results can be extrapolated to other devices and manufacturers.